An Automated Surveillance Strategy to Ide.jpegy Infectious Complications After Cardiac Implantable Electronic Device Procedures. (1st September 2015) - Boggan, Joel C.; Baker, Arthur W.; Lewis, Sarah S.; Dicks, Kristen V.; Durkin, Michael J.; Moehring, Rebekah W.; Chen, Luke F.; Knelson, Lauren P.; Hegland, Donald D.; Anderson, Deverick J.
Abstract : As with surgical procedures, regular surveillance of infectious complications following cardiac implantable electronic device procedures is possible with electronic means combining queries of ICD-9 codes and microbiologic data. Feedback of complication rates may lead to improved patient outcomes. Abstract: Background.  The optimum approach for infectious complication surveillance for cardiac implantable electronic device (CIED) procedures is unclear. We created an automated surveillance tool for infectious complications after CIED procedures. Methods.  Adults having CIED procedures between January 1, 2005 and December 31, 2011 at Duke University Hospital were ide.jpegied retrospectively using International Classification of Diseases, 9th revision (ICD-9) procedure codes. Potential infections were ide.jpegied with combinations of ICD-9 diagnosis codes and microbiology data for 365 days postprocedure. All microbiology-ide.jpegied and a subset of ICD-9 code-ide.jpegied possible cases, as well as a subset of procedures without microbiology or ICD-9 codes, were reviewed. Test performance characteristics for specific queries were calculated. Results.  Overall, 6097 patients had 7137 procedures. Of these, 1686 procedures with potential infectious complications were ide.jpegied: 174 by both ICD-9 code and microbiology, 14 only by microbiology, and 1498 only by ICD-9 criteria. We reviewed 558 potential cases, including all 188 microbiology-ide.jpegied cases, 250 randomly selected ICD-9 cases, and 120 with neither. Overall, 65 unique infections were ide.jpegied, including 5 of 250 reviewed cases ide.jpegied only by ICD-9 codes. Queries that included microbiology data and ICD-9 code 996.61 had good overall test performance, with sensitivities of approximately 90% and specificities of approximately 80%. Queries with ICD-9 codes alone had poor specificity. Extrapolation of reviewed infectious rates to nonreviewed cases yields an estimated rate of infection of 1.3%. Conclusions.  Electronic queries with combinations of ICD-9 codes and microbiologic data can be created and have good test performance characteristics for ide.jpegying likely infectious complications of CIED procedures.